Les mégalithes du Sénégal et de la Gambie dans leur contexte régional - Luc Laporte (OpenEdition, 2017)
Stone architectures of the Senegambian megalithism have long been considered as an autonomous entity in a sector of the African continent where adobe constructions are traditionally favoured. Our knowledge of these monuments has been deeply modified by ten years of archaeological research on the World Heritage site of Wanar (Senegal). This paper review these new elements in their regional context, integrating available data about protohistoric funerary monuments in Senegal as well as in Mali, Guinea, Guinea-Bissau, Liberia, Sierra Leone and even sometimes more widely. The authors have demonstrated – in a more systematic way than in previous work – that several features of the Senegambian funerary customs can find an echo in the West African ethnological record.